Understanding unit-based nurse leader experiences in a psychoeducational group program: a qualitative study - Sawyer, Amanda T.; Bailey, Amanda K.; Harris, Stephanie L. (Frontiers in Organizational Psychology, 2024)
BackgroundA psychoeducational group program for nurse leaders was developed based on the four themes of resilience, insight, self-compassion, and empowerment and involves therapeutic processing with a licensed mental health professional to alleviate burnout symptoms and protect wellbeing. The program was tested in a randomized controlled trial, which included a qualitative component to examine unit-based nurse leaders' perspectives of their job role and their experiences in the psychoeducational group program.MethodsOnline semi-structured interviews with 18 unit-based nurse leaders were conducted after completion of the program. Thematic analysis using the six-step process identified by Braun and Clarke resulted in the establishment of final themes.ResultsThree primary themes emerged from the data analysis: emotional and mental wellbeing, relationships and social support, and professional experiences. There were nine sub-themes, which included temporal exploration of the themes before, during, and after the program as participants experienced transformation and growth. Findings illustrate that unit-based nurse leaders contend with many workplace stressors that impact their mental health. The psychoeducational group program enabled participants to prioritize self-care, contributed to participants feeling empowered to make positive changes in their work and home lives, and fostered a sense of connection and belonging. Participants also expressed a perceived improvement in their ability to be effective leaders.ConclusionsThese qualitative findings can help guide future implementation efforts of wellbeing programs for unit-based nurse leaders.